Pengembangan Video Profil Berbasis Drone untuk Konten Digital Marketing di Media Sosial - Zabidi, Yasrin; Nurdin, Riani; Astuti, Marni; Santoso, Prasidananto Nur; Gunawan, Gunawan; Rengganis, Esa; Mauidzoh, Uyuunul (Pakis Journal Institute, 2025)
The problem in the Community Service activity is that SMA Negeri 1 Wates already has a profile video, but does not yet have a drone-based profile video that displays the profile of SMA Negeri 1 Wates from the air which has its own appeal and uniqueness which will later be used as digital marketing content material in promoting the school. This problem can be overcome by developing a drone-based profile video for digital marketing content. The achievement of this activity is the realization of 3 (three) long versions of SMA Negeri 1 Wates Profile Videos with a duration of 3 minutes 50 seconds, 3 minutes 40 seconds, 2 minutes 21 seconds for digital marketing content on YouTube and the website and 1 (one) short version of SMA Negeri 1 Wates profile video with a duration of 38 seconds for digital marketing content on Instagram, Facebook, TikTok.